Performers' discourses on listening to recordings. (October 2021) - Volioti, Georgia; Williamon, Aaron
How we listen to music and respond to its media and contexts has changed significantly since the invention of sound recording. Today's musicians have countless opportunities to listen to others' interpretations given the vast availability of past and contemporary repertories through the global reach of recordings. This study investigated the extent to which the growing archive of recordings provides a valuable resource for performers' creativity. Although musical performance is a particularly porous domain for influence through either deliberate or spontaneous assimilation of expressive variation from other aural sources, little empirical research exists on influence in performance and specifically on the influence of recordings. Qualitative data were obtained via an online questionnaire to identify how and in what ways the use and influence of recordings have changed over the course of classical performers' training or professional careers. Respondents' ( N = 130) comments were analysed using a thematic inductive approach. The emerging themes reveal an overall increased level of use of recordings now relative to the past, a largely positive contribution of recordings in shaping musical development, including the role of recordings in self-regulated learning, a largely positive attitude to the influence of others' interpretations, a means of developing expressions of self-identity in relation to others and a route to acquiring a more critical and discerning mode of listening to recordings. Implications for music education are discussed in terms of how listening to recordings, in both formal and informal learning contexts, could support advanced musicians' learning through trial and error, enhance creative insight, strengthen self-efficacy, foster metacognitive skills and nurture individuality.